(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
In light of the wide spread of communication technologies, especially social networking sites, which has increased its role and impact on the nature of human relations, as this wide spread of various information has been met with News, ideas ...The nature of social relationships in general and family relationships in particular has changed, and it is noted that social media has a role in narrowing the circle of social relations between families. There is no doubt that in the light of the communication revolution that the world is experiencing now, social media has become a widespread phenomenon affecting the way individuals think and talk to others. this is what made the creators and developers of social media networks lead the new world and formulate its culture (globalization), set its policies and control its economy with their communication tools, which has become a means of controlling the world and imposing the culture of globalization and its values. it is natural in light of this domination that societies are influenced by a culture different from their own.